Designing the Layout of Offshore Protection Structures at Tugu Beach, Air Bangis (Indonesia) using Numerical Simulation - Amri, Afdhal; Mera, Mas (Jurnal Teknik Sipil dan Lingkungan, 2025)
Tugu Air Bangis Beach, located in West Pasaman Regency, has experienced severe coastal erosion caused by wave energy from the Indian Ocean. This condition has resulted in the collapse of several structures along the shoreline and threatens the remaining coastal infrastructure. Mitigation measures are therefore required to maintain shoreline stability and prevent further damage. This study aims to design the layout of coastal protection structures for Tugu Air Bangis Beach using numerical simulations to reduce the impact of wave- and current-induced erosion. The data used in this study include satellite imagery, wind data, tidal elevation data, Digital Elevation Model (DEM) data, and aerial photographs. Tidal flooding (rob) occurred in Padang City and Air Bangis from December 3 to 5, 2021, and the tidal elevation data used for the simulation were obtained from real-time measurements recorded at the Teluk Bayur Station, Padang, between December 1 and 9, 2021. Numerical simulations were performed using the CMS-Wave and CMS-Flow modules in the Surface Water Modelling System (SMS) version 10.1. The simulations were conducted in two stages. The first stage employed the existing structure layout, simulated for 216 hours of model time (equivalent to 36 hours of computer running time). The results indicated that the incoming waves approach the shoreline perpendicularly, suggesting that a breakwater is the most appropriate coastal protection structure. In the second stage, two breakwaters of equal length (200 meters each) and equal distance from the original shoreline (100 meters) were added. The numerical model results showed that this configuration effectively mitigates erosion, as indicated by sediment accumulation along several shoreline segments and the initial formation of a tombolo behind the breakwaters.